In House Training Implementasi Kurikulum Merdeka di SMPN 1 Cisitu Kabupaten Sumedang melalui Pendekatan Komunikasi : - Diah Fatma Sjoraida; Aat Ruchiat Nugraha; Iriana Bakti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In House Training is one of the institution's communication actions in an effort to increase knowledge and strengthen the ability to act in an activity for the internal public (teachers). Education as an activity needs to receive new input to be able to produce student outcomes that are of quality, intelligence and character. To get these results, guidelines and references are needed that are scientifically and practically accountable, one of which is through curriculum content that is competitive for schools. The Merdeka Curriculum, which is a